(untitled) (Academicia Globe: Inderscience Research, 2022)
Myrrh is a gum- resin exudate obtained by cutting in Commiphora myrrha trees belong Burseraceae. The bactericidal activity of Myrrh hexane extract tested against Staphylococcus aureus (S. aureus) , Escherichia coli ( E.coli) and Pseudomonas aeruginosa (Ps. aeruginosa ) . Present study was aimed to determine the active groups of myrrh and their biological activity.